فعالية استخدام البطاقات التعليمية لترقية القدرة على حفظ المفردات العربية لدى طلاب الصف الثامن بالمدرسة الثانوية دار العلوم سيماهبار بوجور - Muhamad zikri afriansyah; Isniyatun Niswah (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2025)
To understand the Arabic language, individuals have varying abilities—some find it easy to comprehend, while others struggle. This is because Arabic is not the native language in Indonesia; differences in letters, pronunciation, and writing systems make it challenging for many to grasp. Therefore, Arabic is considered a foreign language and is one of the subjects that must be taught in Islamic schools, particularly madrasahs, to help students gain a deeper understanding of the language.Based on this background, the research formulates the following problems:(1) What is the effect of using flashcard media in Arabic language subjects for grade VIII students at Darul Ulum School in Bogor?(2) Does the use of flashcards in Arabic language lessons improve the vocabulary memorization ability of grade VIIIC students at Darul Ulum School in Bogor?This study employed a quantitative method using a pre-experimental design (one-group pretest-posttest). The sample consisted of 34 eighth-grade students from Darul Ulum Junior High School in Cimahpar, Bogor. Data collection techniques included observation, test questions, and documentation. Data analysis was conducted using descriptive statistical analysis and inferential non-parametric statistical analysis with the help of SPSS 16.0 through the Wilcoxon Signed-Rank Test.